Respect and criminal justice - Watson, Gabrielle, 1989- (Oxford : Oxford University Press, 2020)
'Respect and Criminal Justice' offers the first sustained examination of the role and value of 'respect' in policing and imprisonment in England and Wales, where the value is elusive but of persisting significance. The text takes the form of a sustained critique of the 'respect deficit' in policing and imprisonment. It is especially concerned with the ways in which both institutions are merely constrained and not characterised by respect. It emerges that both institutions appeal to the word 'respect' - relying on its inclusive ethos in official discourse when it is expedient to do so - but rarely and only superficially address the prior question of what it is to respect and be respected.
This edition also issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on July 10, 2020).
Keywords: Criminal justice, Administration of -- Philosophy; Police -- England; Police -- Wales; Imprisonment -- England; Imprisonment -- Wales; Respect; True Crime; Social services & welfare, criminology